Cover Feature: Biomimetic Self‐Cleaning Anisotropic Solid Slippery Surface with Excellent Stability and Restoration (ChemPhysChem 7/2019). Issue 7 (8th April 2019) - Guo, Pu; Sun, Yimin; Zhang, Yuqi; Hou, Xueyan; Song, Yanwei; Wang, Ji‐Jiang
Abstract : The Cover Feature illustrates an anisotropic solid slippery surface based on paraffin wax‐incorporated paper with directional micro‐grooves, inspired by epicuticular wax on the surface of land plant leaves. This material shows excellent anisotropic sliding behavior and self‐cleaning effect for both of hydrophilic and hydrophobic contaminants. More information can be found in the Article by P. Guo et al. on page 946 in Issue 7, 2019 (DOI: 10.1002/cphc.201900098 ).